Preoperative bariatric surgery programme barriers facing Pacific patients in Auckland, New Zealand as perceived by health sector professionals: a qualitative study. Issue 11 (2nd November 2019) - Taylor, Tamasin; Wrapson, Wendy; Dewes, Ofa; Taufa, Nalei; Siegert, Richard J
Abstract : Minority ethnic patient groups typically have the highest bariatric surgery preoperative attrition rates and lowest surgery utilisation worldwide. Eligible patients of Pacific Island ethnicity (Pacific patients) in New Zealand (NZ) follow this wider trend. Objectives: The present study explored structural barriers contributing to Pacific patients' disproportionately high preoperative attrition rates from publicly-funded bariatric surgery in Auckland, NZ. Setting: Publicly-funded bariatric surgery programmes based in the wider Auckland area, NZ. Design: Semi-structured interviews with health sector professionals (n=21) were conducted. Data were analysed using an inductive thematic approach. Results: Two primary themes were identified: (1) Confidence negotiating the medical system, which included Emotional safety in clinical settings and Relating to non-Pacific health professionals and (2) Appropriate support to achieve preoperative goals, which included Cultural considerations, Practical support and Relating health information . Clinical environments and an under-representation of Pacific staff were considered to be barriers to developing emotional safety, trust and acceptance of the surgery process with patients and their families. Additionally, economic deprivation and lower health literacy impacted preoperative goals. Conclusions: Health professionals' accounts indicated that Pacific patients face substantial levels of disconnection in bariatric surgery programmes. Increasing representation of Pacific ethnicity by employing more Pacific health professionals in bariatric teams and finding novel solutions to implement preoperative programme components have the potential to reduce this disconnect. Addressing cultural competency of staff, increasing consultancy times and working in community settings may enable staff to better support Pacific patients and their families. Programme structures could be more accommodating to practical barriers of attending appointments, managing patients' preoperative health goals and improving patients' health literacy. Given that Pacific populations, and other patients from minority ethnic backgrounds living globally, also face high rates of obesity and barriers accessing bariatric surgery, our findings are likely to have broader applicability.